Strategy Of PR Communications For The National Narcotics Agency (BNN) Deli Serdang Regency In Socializing The Prevention Program For The Eradication Of Abuse Of Illegal Circulation Of Narcotics (P4GN) Through Social Media (International Journal of Cultural and Social Science, 2022)
This study uses qualitative methods in collecting the data needed by researchers using interview techniques while in the discussion using descriptive methods that describe the conditions that occur in the field systematically. Informants in this study were the head of the general sub-section of coordinator and public relations as well as people from the BBN community in Deli Serdang Regency. The communication strategy used by BBN in socializing the P4GN program through social media is content providing content through types of content in the form of video posters and various things about P4GN to educate social media followers about healthy living. How to stay away from drugs, how to become a family that has high resilience and also how the village community can shine clean from drugs.